Buyers' property asset purchase decisions: an empirical study on the high-end residential property market in Hong Kong. Issue 1 (2nd January 2016) - Jayantha, Wadu Mesthrige; Lau, Jia Ming
ABSTRACT: Demand for luxury housing units from the upper and upper-middle income groups in Hong Kong has been increasing over the last few years. as the market cannot satisfy demand, some prospective buyers have turned their attention to "special" housing units. this research paper attempts to investigate buyers' preferences for two types of "special" units, namely duplex units and adjoining flats. the study investigates the price premiums paid by the buyers, and examines the effects of these special units on property price. the study employs two hedonic price models: one measuring the buy- ers' preference on duplex units and the other one measuring buyers' preference on adjoining flats. The results show that buyers are willing to pay a larger premium for special residential units: HK588/ft 2 more for a duplex unit and HK934/ft 2 more for an adjoining property unit, respectively. furthermore, a relatively larger premium is found for adjoining flats compared to duplex units. This implies that a property unit, purchased as an adjoining flat can add more value to the property price (in terms of s per sq. ft.) compared with being a duplex unit.